2007
DOI: 10.1177/0961203306073136
|View full text |Cite
|
Sign up to set email alerts
|

New immunosuppresor strategies in the treatment of murine lupus nephritis

Abstract: Renal involvement in systemic lupus erythematosus is a common complication that significantly worsens morbidity and mortality. Although treatment with corticosteroids and cytotoxic drugs may be useful in many cases, morbidity associated with these drugs and the relapsing nature of the disease make it necessary to develop new treatment strategies. Five-month old female NZB/W F1 mice were divided into the following groups: CYP group (n = 10), cyclophosphamide (CYP) 50 mg/kg intraperitoneally every 10 days; RAPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 27 publications
7
51
0
2
Order By: Relevance
“…Although glomerular injury is always accompanied by interstitial inflammation in lupus nephritis, the pathogenesis of these entities and their responses to some treatments seem to be different. For example, treatment with oral fingolimod (FTY720) and with the targeted murine C3 complement inhibitor CR2-Crry was found to be more effective in ameliorating glomerular injury than in controlling interstitial infiltrates and lesions (37,38). Otherwise, blockade of CCR1 could selectively halt interstitial leukocyte recruitment and fibrosis but not glomerular injury in MRL/lpr mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although glomerular injury is always accompanied by interstitial inflammation in lupus nephritis, the pathogenesis of these entities and their responses to some treatments seem to be different. For example, treatment with oral fingolimod (FTY720) and with the targeted murine C3 complement inhibitor CR2-Crry was found to be more effective in ameliorating glomerular injury than in controlling interstitial infiltrates and lesions (37,38). Otherwise, blockade of CCR1 could selectively halt interstitial leukocyte recruitment and fibrosis but not glomerular injury in MRL/lpr mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin was described on the one hand to limit autoimmune disease 7 but on the other hand to have the potential to Figure 1. Rapamycin started on the day of immunization significantly reduces albuminuria and PAS-positive deposits in glomeruli.…”
Section: Start Of Rapamycin On the Day Of Immunization (Group 1)mentioning
confidence: 99%
“…4,5 In addition, rapamycin has been shown to inhibit the proliferation of B cells and has very recently been described to be a potential ther-apeutic option in systemic lupus erythematosus. 6,7 Both studies evaluated the effect of rapamycin or its derivative everolimus on lupus-prone mice, namely NZB/W F1 or B6.Sle1 z .Sle3 z mice. 6,7 They provided evidence that rapamycin treatment significantly decreased autoantibody production, thereby reducing glomerulonephritis (GN) 6,7 ; however, further evidence suggested that rapamycin can lead to an increase in proteinuria followed by a decline in renal function.…”
mentioning
confidence: 99%
See 2 more Smart Citations